The influence of human resource competence, accounting digitalization, and internal control on the quality of financial statements of MSMEs in Gunungpuyuh District, Sukabumi City - Nayana, Septyas Fatihah Putri; Hardianto, Ade Manggala; Ardiansyah, Miri; Adhie, Leviandi; Novitasari, Yuli (Privietlab, 2026)
This study aims to assess the impact of “Human Resource Competence, Accounting Digitalization, and Internal Control on the Quality of Financial Reports for micro, small, and medium enterprises (MSMEs) in the Gunungpuyuh District of Sukabumi City”. The quality of financial reports plays a crucial role for MSMEs, as it supports accurate decision-making, ensures business operational continuity, and facilitates access to external funding sources. This study employs a quantitative approach through survey methods and multiple linear regression analysis, which allows for the measurement of the intensity and significance of the relationships between the independent and dependent variables. Data were collected from 100 respondents who are MSME actors in the Gunungpuyuh District, representing various business sectors and scales, thus providing a comprehensive view of the local MSME landscape. The research findings indicate that “Human Resource Competence, Accounting Digitalization, and Internal Control each have a positive and significant partial effect on the Quality of Financial Reports, with significance values of 0.001, 0.004, and 0.001, respectively. Collectively, these three independent variables also significantly influence the Quality of Financial Reports, as evidenced by the F-test with a significance value of 0.000. The coefficient of determination indicates that 82.4% of the variation in the Quality of Financial Reports can be explained by this research model, while the remaining 17.6% is influenced by other factors not addressed in this study”. To improve financial management practices among MSMEs in this region, targeted interventions are needed in three areas: human resource competency, effective accounting digitization, and internal control. This will help enhance the quality of financial reports for MSMEs.